TECHNIQUES IN TEACHING VOCABULARY AT THE FIRST GRADE SD CITRA BANGSA SCHOOL PRINGSEWU - Tiara Noviarini (Jurnal Smart, 2017)
Abstract   This study reports on research results aimed at investigating the techniques used by a teacher and techniques employed implemented to be teach vocabulary to students, as well as students’ responses in employing those techniques. Interview, observation, and documentation were carried out to collect the data. The findings indicate that the teacher applied various techniques with various responses in teaching vocabulary. In teaching vocabulary, the teacher mostly employed Repetition drill, vocabulary networks, guess the word, guess the picture, and sing a song. It is relevant to procedure of techniques in teaching English vocabulary. Most of the students of first grade give positive response, they were very enthusiastic and motivated by the techniques used by the teacher.   Keywords: Teaching techniques, vocabulary, presenting vocabulary.